2019
DOI: 10.1186/s42269-019-0187-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bacillus species for controlling root-knot nematode Meloidogyne incognita in eggplant

Abstract: Background: Eggplant (Solanum melongena L.) is one of the important vegetable crops infected by Meloidogyne incognita all over the world, including Egypt. Chemical nematicides frequently cause environmental pollution and toxic hazards to human, plants, and animals; certain biocontrol agents that are environmentally friendly and safe to humans and animals were tested against the root-knot nematode Meloidogyne incognita in eggplant. Objective: This work is aimed to determine the nematicidal activity of Bacillus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…In vitro B. velezensis BZR 86 caused 98% mortality of M. incognita J2 following a 24-h exposure to a 9 × 10 7 CFU mL −1 bacterial density [ 55 ]. In our study the nematicidal effect of B. velezensis BZR 86 was also confirmed on cucumber and tomato in soil, in agreement with previous studies that reported a significant suppressiveness of Bacillus strains on root-knot nematode eggs, J2 and root galls on cucumber [ 10 , 55 ], tomato [ 16 , 17 , 53 , 58 ], eggplant [ 15 , 59 ] and hendi [ 60 ]. The mechanisms underlying the RKN suppression by Bacillus strains can be different.…”
Section: Discussionsupporting
confidence: 91%
“…In vitro B. velezensis BZR 86 caused 98% mortality of M. incognita J2 following a 24-h exposure to a 9 × 10 7 CFU mL −1 bacterial density [ 55 ]. In our study the nematicidal effect of B. velezensis BZR 86 was also confirmed on cucumber and tomato in soil, in agreement with previous studies that reported a significant suppressiveness of Bacillus strains on root-knot nematode eggs, J2 and root galls on cucumber [ 10 , 55 ], tomato [ 16 , 17 , 53 , 58 ], eggplant [ 15 , 59 ] and hendi [ 60 ]. The mechanisms underlying the RKN suppression by Bacillus strains can be different.…”
Section: Discussionsupporting
confidence: 91%
“…However, it seems that the higher dosage applied the lowest the population (Table 4). Similar finding reported by El-Nagdi and Abd-El-Khair [13] that Meloidogyne spp. population with 30 ml Bt suspension treatment were195 in root and 407 in rhizosphere.…”
Section: Meloidogyne Spp Populationsupporting
confidence: 91%
“…Researchers reported that Bt has strong effect on Meloidogyne sp. mortality [7,13,14]. Reports on the use of Bt to control Meloidogyne spp.…”
Section: Introductionmentioning
confidence: 99%
“…So far, some secondary metabolites can also trigger an immune reaction in the host plants, which leads to systemic resistance (Choudhary and Johri, 2009;Adam et al, 2014), rendering the plant less susceptible to pathogen infection. Some examples also point to enhanced beneficial effects combining both the plant growth attributes and their effect on nematodes control after coinoculation of different rhizobacteria species (Ansari and Ahmad, 2019;El-Nagdi and Abd-El-Khair, 2019;Topalovicé t al., 2020). Plant growth promoting rhizobacteria (PGPR; Lim and Kim, 2009) facilitate plant development by producing phytohormones (auxins, cytokines, ethylene, abscisic acid, etc.…”
Section: Introductionmentioning
confidence: 99%